Perancangan Interior Creativity Place dengan Edukasi Robotik, Scrapbook, dan Puzzle di Surabaya - Theresia Claudia Hindarto; Stephanus P Honggowidjaja (Intra, 2016)
The phenomenon of gadgets that coming into Indonesia make people, especially children particularly really liked it. This can be seen with the number of children in public space who using it. The frequency of using gadgets will disturb the children psychological, reduced creativity, the power of concentration is reduced, and they will tend to be selfish because they not notice others.Therefore it needs place for the children to be able to exercise their creativity, concentration, increase motor skills and socialization.